Morphological Analysis of Inflectional and Derivational Morphemes on Instagram s Captions - Rifanda Cynthia Goni; Sulis Triyono; Wening Sahayu (Journal of English Language Teaching, Literature and Culture, 2022)
Morphological process in word formation is not limited to the long text novel or story but it could be founded into shorter sentences such as Instagram s captions Inflectional and derivational morphemes are a part of morphological process that used as a word formation This study used a qualitative descriptive method to look for the types and the function of inflectional and derivational morphemes The data was collected from Barack Obama s captions on Instagram post and analysed by using the theory of Victoria Fromkin Rodman R and Hymas N in An Introduction to Language 2014 The result showed that there were forty live kinds of inflectional morphemes and there were thirty four kinds of derivational morphemes so there were eighty nine overall regarded to inflectional and derivational morphemes However there are not all types of inflectional morphemes that can be found in this study The inflectional morphemes were to give grammatical information and do not the part of speech In contras the derivational morpheme is the complex one because it can change the meaning and category of speech when some morphemes attached< p>